Immunotherapy for the treatment of Alzheimer’s disease: amyloid-β or tau, which is the right target? - Castillo-Carranza, Diana L (Immunotargets Ther, 2013)
Alzheimer’s disease (AD) is characterized by the presence of amyloid plaques composed mainly of amyloid-β (Aβ) protein. Overproduction or slow clearance of Aβ initiates a cascade of pathologic events that may lead to formation of neurofibrillary tangles, neuronal cell death, and dementia. Although immunotherapy in animal models has been demonstrated to be successful at removing plaques or prefibrillar forms of Aβ, clinical trials have yielded disappointing results. The lack of substantial cognitive improvement obtained by targeting Aβ raises the question of whether or not this is the correct target. Another important pathologic process in the AD brain is tau aggregation, which seems to become independent once initiated. Recent studies targeting tau in AD mouse models have displayed evidence of cognitive improvement, providing a novel therapeutic approach for the treatment of AD. In this review, we describe new advances in immunotherapy targeting Aβ peptide and tau protein, as well as future directions.